Nanoreinforcements of Two-Dimensional Nanomaterials for Flame Retardant Polymeric Composites: An Overview - Shaolin Lu; Wei Hong; Xudong Chen (Advances in Polymer Technology)
Polymer materials are ubiquitous in daily life. While polymers are often convenient and helpful, their properties often obscure the fire hazards they may pose. Therefore, it is of great significance in terms of safety to study the flame retardant properties of polymers while still maintaining their optimal performance. Current literature shows that although traditional flame retardants can satisfy the requirements of polymer flame retardancy, due to increases in product requirements in industry, including requirements for durability, mechanical properties, and environmental friendliness, it is imperative to develop a new generation of flame retardants. In recent years, the preparation of modified two-dimensional nanomaterials as flame retardants has attracted wide attention in the field. Due to their unique layered structures, two-dimensional nanomaterials can generally improve the mechanical properties of polymers via uniform dispersion, and they can form effective physical barriers in a matrix to improve the thermal stability of polymers. For polymer applications in specialized fields, different two-dimensional nanomaterials have potential conductivity, high thermal conductivity, catalytic activity, and antiultraviolet abilities, which can meet the flame retardant requirements of polymers and allow their use in specific applications. In this review, the current research status of two-dimensional nanomaterials as flame retardants is discussed, as well as a mechanism of how they can be applied for reducing the flammability of polymers.